Evaluation of Mechanical and Thermal Properties of Hydroxyapatite-levan Composite Bone Graft - Song, Younghoon; Joo, Kye; Seo, Jeong Hyun (Biotechnology and bioprocess engineering, 2021)
Biodegradable materials have been received great attention as bone graft substitutes for bone regeneration and tissue engineering. However, their low mechanical property remains a major challenge for the use in load-bearing applications. Here, we developed mechanically reinforced composite scaffold containing adhesive levan as a binder for sintered hydroxyapatite (sHAp) and then examined the mechanical and thermal properties of the composite scaffold. We found that sHAp-levan composite scaffold exhibited remarkably enhanced mechanical strength, which is similar to that of polymethyl methacrylate (PMMA) bone cement. This composite scaffold can be utilized as a promising bone graft for bone regeneration and tissue engineering.